Inclusive planning: African policy inventory and South African mobility case study on the exclusion of persons with disabilities - Marianne J. W. A. Vanderschuren; Obiora A. Nnene (BMC, 2021)
Abstract Background The Sustainable Development Goals (SDGs) and universal design (UD) principles call for inclusive planning. Within the transportation field, this includes the development or improvement of facilities that accommodate people with disabilities. Between 10% and 20% of the African population is affected by disabilities. A lack of understanding of the needs of people with disabilities leads to isolation. Within the transportation field, isolation manifests itself as a reduction in trip-making. Methods This paper investigates the availability of transport policies and guidelines in 29 different African countries, focusing on the inclusion of persons with disabilities. A desktop study was conducted creating heat maps for 29 African countries, followed by the analysis of secondary data in the case study area, South Africa, demonstrating that the lack of adequate policies, guidelines, and appropriate implementation leads to a lack of accessibility, opportunities, and social isolation, measured through trip frequencies. Results The data analysed revealed that many African countries omit, or only superficially include, people with disabilities in their transport policy framework. Ghana has the most inclusive People with Disabilities Act, while South Africa is most inclusive regarding their planning and design of transport facilities and services. In South Africa, 4.5% of the population did not travel at all in the 7 days before the interview, as disability or age prevented them from doing so, or due to a lack of appropriate travel services. When comparing the trip rates per week, people with disabilities travel significantly less, between 27.2% and 65.8%, than their abled counterparts. Conclusions The study reveals that people with disability live less integrated, more isolated lives due to the lack of acknowledgement in the transport policy framework and accommodation in infrastructure and services. The results underpin the need for disability-inclusive planning in the African context and provide recommendations for actions that mitigate the isolation challenges faced by people with disabilities. Municipalities play a crucial role in improving the quality of life for people with disabilities.